Efficacy and safety of dupilumab for the treatment of uncontrolled asthma: a meta-analysis of randomized clinical trials - Xiao-feng Xiong; Min Zhu; Hong-xia Wu; Li-li Fan; De-yun Cheng (Respiratory Research, 2019)
Abstract Background Several recent clinical trials have assessed the effects of dupilumab in uncontrolled asthma, but reached no definite conclusion. We therefore conducted this meta-analysis to evaluate the overall efficacy and safety of dupilumab for the treatment of uncontrolled asthma. Methods All randomized controlled trials were included. Standard mean differences (SMD) or relative risks (RR) were calculated using Fixed-or random-effects models. Results Five studies involving 3369 patients were identified. Pooled analysis showed significant improvements in the first-second forced expiratory volume (FEV1) (SMD = 4.29, 95% CI: 2.78–5.81) and Asthma Quality of Life Questionnaire scores (SMD = 4.39, 95% CI: 1.44–7.34). Dupilumab treatments were also associated with significantly decreased 5-item Asthma Control Questionnaire scores (SMD = − 4.95, 95% CI: − 7.30 to − 2.60), AM and PM asthma symptom scores (SMD = − 5.09, 95% CI: − 6.40 to − 3.77; SMD = − 4.92, 95% CI: − 5.98 to − 3.86, respectively), and severe exacerbation risk (RR = 0.73; 95% CI: 0.67–0.79) compared with placebo, with similar incidence of adverse events (RR = 1.0; 95% CI: 0.96–1.04). Conclusion Dupilumab treatment is relatively well-tolerated and could significantly improve FEV1, symptoms, asthma control, and quality of life, and reduced severe exacerbation risk in patients with uncontrolled asthma.